2017
DOI: 10.4236/ojce.2017.73027
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Metakaolin from Saaba (Burkina Faso) over Physico-Mechanical and Durability Properties of Mortars

Abstract: The paper evaluates the feasibility of reducing clinker in the Portland Cement production using local metakaolin in Burkina Faso. Standardized testing methods have been used for this purpose, and experiments were performed on mortar prisms containing different amounts of metakaolin. Important results about the physical, mechanical and durability characterization of blended mortars were carried out in this study. The obtained results are discussed based on available literature data. These results have shown inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…From the filtrate, the remaining unreacted portlandite was extracted with saccharose and titrated by a 0.1 N hydrochloric acid solution according to equation (Eq. 1) 18 , 19 , each value considered being the average of three test results made under the same conditions. On the other hand, the precipitated products of reactions with K, Kc, K 10 and Kc 10 , denoted as K′, Kc′, K 10 ′ and Kc 10 ′ respectively, were analyzed by XRD to identify constitutive phases.…”
Section: Methodsmentioning
confidence: 99%
“…From the filtrate, the remaining unreacted portlandite was extracted with saccharose and titrated by a 0.1 N hydrochloric acid solution according to equation (Eq. 1) 18 , 19 , each value considered being the average of three test results made under the same conditions. On the other hand, the precipitated products of reactions with K, Kc, K 10 and Kc 10 , denoted as K′, Kc′, K 10 ′ and Kc 10 ′ respectively, were analyzed by XRD to identify constitutive phases.…”
Section: Methodsmentioning
confidence: 99%
“…The geotechnical properties of clay materials before calcination are listed in Table 3. These results indicate that the first three clay materials (A1, A2, A3) have the highest plasticity indexes (17)(18)(19)(20)(21)(22), while the clay material A4 has the lowest plasticity index (8). Thus, the first three materials may have a higher content of clay minerals, while the last material has a lower plasticity index and thus possibly lower content of clay minerals [11,33].…”
Section: Geotechnical and Physical Properties Of Claysmentioning
confidence: 98%
“…Numerous studies have shown that industrial by-products, such as silica fume, fly ash, rice husk ash or simply natural materials, such as tuff, granite dust and limestone Sustainability 2022, 14, 2308 2 of 21 fillers, among others, meet the specific criteria of reactivity and/or filler [5][6][7][8][9]. These byproducts can therefore be used as partial substitutes for clinker or supplementary cementing materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Burkina Faso, clay materials are already the subject of scientific work for their valorization [7,8,9] in construction. However, there is little literature on the use of Tuff in the cement industry, except in Algeria, where more than 50% of the cement plants that use calcareous Tuffs as pozzolans in the manufacture of cement are found [10].…”
Section: Introductionmentioning
confidence: 99%